Personal Safety Skill Sebagai Pencegahan Kekerasan Seksual Pada Remaja Putri - Nurul Maurida; Irwina Angelia Silvanasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
Sexual violence has become a global concern. The number of sexual violence is statistically more dominantly experienced by women. Young women need to have the ability to prevent sexual violence. The purpose of this study was to identify the personal safety skills of young women. This research is a quantitative descriptive study with a survey approach. The research sample was 150 young women using a sampling technique in the form of stratified random sampling. Research respondents were divided based on educational strata, ranging from junior high school (SMP), high school (SMA), and college (PT). Each stratum is represented by 50 young women. The research was conducted at SMPN 1 Kalisat, SMK Bangsalsari, and dr. Soebandi. The three research sites are located in Jember Regency. Collecting data using a research instrument in the form of a personal safety skill questionnaire. The results showed that in personal safety skills, some of the recognize indicators were lacking (53.3%), the resist indicators were partly good (56.0%), and the report indicators were partly lacking (55.3%). Personal safety skills in young women can be taught by involving various parties, such as teachers and parents. Personal safety skills if developed properly can keep young women away from perpetrators of sexual violence